Indications for allo- and auto-SCT for haematological diseases, solid tumours and immune disorders: current practice in Europe, 2015 - Sureda, Anna; Dreger, Peter (Bone marrow transplantation, 2015)
This is the sixth special report that the European Society for Blood and Marrow Transplantation regularly publishes on the current practice and indications for haematopoietic SCT for haematological diseases, solid tumours and immune disorders in Europe. Major changes have occurred in the field of haematopoietic SCT over the last years. Cord blood units as well as haploidentical donors have been increasingly used as stem cell sources for allo-SCT, thus, augmenting the possibility of finding a suitable donor for a patient. Continuous refinement of conditioning strategies has also expanded not only the number of potential indications but also has permitted consideration of older patients or those with co-morbidity for a transplant. There is accumulating evidence of the role of haematopoietic SCT in non-haematological disorders such as autoimmune diseases. On the other hand, the advent of new drugs and very effective targeted therapy has challenged the role of SCT in some instances or at least, modified its position in the treatment armamentarium of a given patient. An updated report with revised tables and operating definitions is presented.
Gesehen am 25.06.2020